Penggunaan Media Audio Visual dalam Penerapan Pembelajaran Fiqih di Madrasah Ibtidaiyah - Rubi Awalia (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2024)
This study was conducted to describe the use of audio-visual media in fiqh learning in Madrasah Ibtidaiyah. The focus of this study is: 1) How is fiqh learning planning using audio-visual media for students in Madrasah Ibtidaiyah, 2) How is fiqh learning implementation using audio-visual for students in Madrasah Ibtidaiyah, 3) How is fiqh learning evaluation for students in Madrasah Ibtidaiyah. This study uses qualitative research with descriptive qualitative research type. Determination of research subjects in this study was done purposively. Data collection techniques used observation, interviews, and documentation. Data analysis, researchers used the data analysis model of Miles, Huberman, and Saldana including: Data Condensation, Data Presentation (Display), Conclusion Drawing (Conclusions Drawing). The validity of the data in this study used source triangulation and technique triangulation. The research results show that: planning for fiqh learning using audio-visual media for students in Islamic Elementary Schools includes: preparing a one-year and one-semester material schedule, determining fiqh learning targets by developing lesson plans (RPP), establishing learning objectives, developing engaging materials, determining learning media to be used, determining practical methods, and so on. Implementing fiqh learning using audio-visual media in Islamic Elementary Schools includes: arranging students in class into groups, producing relevant media, explaining fiqh material using a projector, conducting Q&A sessions, and practical work. Evaluation of fiqh learning using audio-visual media for students in Islamic Elementary Schools involves several evaluations: formative evaluation through questions administered at the end of the lesson, including written tests, oral tests, and practical work; and summative evaluation, which includes tests administered at the end of the semester. Assessment of student attitudes, knowledge, and skills.